2009
DOI: 10.1007/s10585-009-9248-9
|View full text |Cite
|
Sign up to set email alerts
|

Osteoblast-induced EGFR/ERBB2 signaling in androgen-sensitive prostate carcinoma cells characterized by multiplex kinase activity profiling

Abstract: Bone metastases in prostate cancer are predominantly osteoblastic. To study regulatory mechanisms underlying the establishment of prostate cancer within an osteoblastic microenvironment, human androgen-sensitive prostate carcinoma cells (LNCaP) were treated with culture medium conditioned by human osteoblast-derived sarcoma cells (OHS), and activated signalling pathways in the carcinoma cells were analyzed using microarrays with tyrosine kinase substrates. Network interaction analysis of substrates with signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 42 publications
(57 reference statements)
2
12
1
Order By: Relevance
“…In this study, hypothesizing that hypoxic tumor signaling mediates both radiation resistance and metastatic progression in rectal cancer, and using previously acquired data [8], we endeavored to correlate the individual patient’s tumor tyrosine kinase activity to the DTC status. In two previous works applying the array technology with tyrosine kinase substrates, we were able to calculate basal kinase activity data and correlate with the biological parameters of interest [8, 15]. In the present study, however, after normalization of basal phosphosubstrate level read-outs, no difference was found among the study patients when comparing those with and without DTC (data not shown).…”
Section: Discussioncontrasting
confidence: 42%
“…In this study, hypothesizing that hypoxic tumor signaling mediates both radiation resistance and metastatic progression in rectal cancer, and using previously acquired data [8], we endeavored to correlate the individual patient’s tumor tyrosine kinase activity to the DTC status. In two previous works applying the array technology with tyrosine kinase substrates, we were able to calculate basal kinase activity data and correlate with the biological parameters of interest [8, 15]. In the present study, however, after normalization of basal phosphosubstrate level read-outs, no difference was found among the study patients when comparing those with and without DTC (data not shown).…”
Section: Discussioncontrasting
confidence: 42%
“…This may be performed by targeted phosphoproteome investigations with specific antibodies, which in its most simplistic form may be undertaken by western immunoblotting [40,65]. Alternatively, investigations of phenotypic events may be carried out by designated functional bioassays.…”
Section: The Kinase Substrate Array Technologymethodological Challengesmentioning
confidence: 99%
“…Histone deacetylase-1 (HDAC1) is association with SP1 was much weaker in lymph node metastatic than in nonmetastatic prostate cancer [56]. Our experimental data suggests induction of signalling activity via EGFR in prostate tumor cells and may provide a rationale for the use of EGFR inhibition in systemic prevention or treatment of lymph node metastatic [57]. In particular our experiments observed a properly designed inhibitor of nuclear receptor subfamily 5 (NR5A1) may be predicted to have therapeutic utility in the treatment of metastatic lymph node through suppression of androgen receptor.…”
Section: Resultsmentioning
confidence: 99%